Book Value Categories and the Acceptance of Technological Changes in English Book Production - Rosenberg, Simon (Muensteraner Monographien zur englischen Literatur / Muenster Monographs on English Literature, 2020)
For more than 20 years now, the publishing industry has been highly influenced by innovations in digital technology. This is not the first time that technological changes affect the book trade. Both the printing press and industrialized production methods vitally changed the book industry in their time. With a macroscopic, comparative approach, this book looks at the transitional phases of the book of the fifteenth and nineteenth centuries to locate distinctive patterns in the acceptance of new technologies. Using specific book value categories, which shape the acceptance context of innovations in book production, helps us find continuities and discontinuities of these patterns. It also offers a better understanding of current developments in publishing in the digital age.